O concerto para violão e pequena orquestra de Heitor Villa Lobos: uma análise do diálogo entre violão e orquestra - Leonardo Souza Amorim (2019)
The present work deals with aspects of the relationship between writing and performance in Heitor Villa-Lobos Concerto for guitar and small orchestra through aesthetic, technical-idiomatic and textural analysis, with the purpose of presenting the characteristics of the dialogue between the guitar and the orchestra. The research is developed from the survey of compositional strategies that Villa-Lobos used so that the guitar - with its specific idiom - could cope with an orchestra. This information will serve as a basis for a comparison of the Villa-Lobos Concert with three other works: Concierto de Aranjuez (J. Rodrigo), Concerto nº 1 in Ré major (M. Castelnuovo-Tedesco) and Concierto Del Sur (M. M. Ponce), chosen for being relatively contemporary, preceding the Villa-Lobos Guitar Concerto for little more than a decade, and for sharing a similar aesthetic line. These comparisons aim to show common procedures and may reveal how Villa-Lobos and the other composers acted to balance two very disparate sound sources, eventually presenting the limits present in the Villa-Lobos Concerto. We hope that this research can help interpreters in the understanding of the work, contributing to its execution and continuous dissemination.